2015
DOI: 10.1080/1573062x.2015.1049279
|View full text |Cite
|
Sign up to set email alerts
|

Defining green roof detention performance

Abstract: Although it is widely accepted that the detention performance of green roofs is of interest to stormwater engineers and planners, no single metric allows detention to be unambiguously defined. Detention effects are highly sensitive to rainfall characteristics and antecedent conditions, and individual roofs typically exhibit wide variations in detention performance between storm events. This paper uses a straightforward hydrological model to explore two alternative approaches to describing detention performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 17 publications
(35 reference statements)
1
77
0
2
Order By: Relevance
“…There is a large inter-event variability shown in most reported studies with reported retention from 0 to 100%, showing a decrease in retention with increasing event sum precipitation [9,21,26,27], but also, other factors such as antecedent soil moisture content are found to be important.…”
Section: Retention Performancementioning
confidence: 99%
See 4 more Smart Citations
“…There is a large inter-event variability shown in most reported studies with reported retention from 0 to 100%, showing a decrease in retention with increasing event sum precipitation [9,21,26,27], but also, other factors such as antecedent soil moisture content are found to be important.…”
Section: Retention Performancementioning
confidence: 99%
“…Detention performance in the field is closely linked to the retention performance, as the initial losses by retention will be included in the detention metrics. Stovin, et al [9] studied four different U.K. climates with a green roof detention model and showed that locations that experienced higher levels of retention also demonstrated improved detention. Feitosa and Wilkinson [42] modelled green roofs in the HYDRUS-1D software modelling water flow in porous media and showed that runoff peak attenuation was severely reduced at high antecedent soil moisture conditions.…”
Section: Retention Performancementioning
confidence: 99%
See 3 more Smart Citations